Potential for Rehabilitation Management Utilizing A Theory of Planned Behavior Approach Via Telehealth in Home Treatment-Based Diabetes Management: A Literature Review - Wildana, Fahmi; Lutfian; Azizah, Aufa; Oktaviana, Essarani (Universitas Nahdlatul Ulama Surabaya, 2024)
iabetes Mellitus is a metabolic disorder characterized by insufficient insulin production or ineffective utilization of insulin, resulting in elevated blood glucose levels. The prevalence of Diabetes Mellitus continues to rise annually, highlighting the urgent issue of inadequate blood sugar control among diabetic patients. Ineffective management of blood glucose levels poses significant risks for complications and adversely affects the quality of life of individuals with diabetes. This article employs a literature review methodology to explore the potential of rehabilitation management for diabetic patients. A comprehensive literature search was conducted across various databases, including Google Scholar, Science Direct, PubMed, and ProQuest. The search utilized keywords such as